2019
DOI: 10.14218/jcth.2018.00060
|View full text |Cite
|
Sign up to set email alerts
|

Role of Radiotherapy in the Treatment of Hepatocellular Carcinoma

Abstract: The role of radiotherapy in the treatment of hepatocellular carcinoma (HCC) has evolved over the past few decades with the advancement of technology and improved imaging. Radiotherapy can offer high local control rates in unresectable HCC, including cases with major vascular involvement, and can provide a modality to help bridge patients to potentially curative resection or transplantation. In metastatic cases, radiotherapy can provide good palliation. This review focuses on the common radiotherapy treatment m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 105 publications
0
34
0
Order By: Relevance
“…IMRT is an advanced technique that uses modulated beams which allow for more improved target coverage, more conformal radiation dose distribution, and better radiation dose sparing of critical normal structures other than the liver. The effectiveness of postoperative adjuvant RT in reducing the recurrence and improving the OS has been well documented in various studies [26][27][28][29][30]. Moreover, adjuvant RT following hepatectomy could efficiently improve the relapse free survival (RFS) and overall survival (OS) in HCC patients with MVI compared with TACE [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…IMRT is an advanced technique that uses modulated beams which allow for more improved target coverage, more conformal radiation dose distribution, and better radiation dose sparing of critical normal structures other than the liver. The effectiveness of postoperative adjuvant RT in reducing the recurrence and improving the OS has been well documented in various studies [26][27][28][29][30]. Moreover, adjuvant RT following hepatectomy could efficiently improve the relapse free survival (RFS) and overall survival (OS) in HCC patients with MVI compared with TACE [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the most common primary malignant tumor of the liver, accounting for ~85% of all cases (36). The high mortality rate of liver cancer is mainly associated with tumor invasion, metastasis and tumor recurrence after surgical resection (6,37). In recent years, a number of studies have confirmed that the CSN superfamily is widely involved in the regulation of several important intracellular pathways, including cell proliferation, migration, invasion and signal transduction, and plays an important role in tumor development (13,(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high malignancy, high invasive potential, and early metastasis onset of HCC, many patients are unable to receive radical resection in a timely manner (32,35). The high mortality rate of patients is due mainly to tumor invasion, metastasis and recurrence after surgical resection (36,37). Researchers are urgently exploring therapeutic targets to improve the diagnosis and treatment of HCC.…”
Section: Discussionmentioning
confidence: 99%